Film/Video-Based Therapy and Trauma research and practice - Cohen, Joshua L. (New York, NY Routledge, an imprint of the Taylor & Francis Group, 2023)
This book uses film/video-based therapy to help build resilience in facing personal, communal, national, and global trauma triggers. Offering a rich and diverse range of perspectives on trauma, this volume advocates positive social change using therapeutic techniques in filmmaking as well as film/video-based therapy, in conjunction with expressive art therapies such as drama, dance, music, painting, drawing, and more. Chapter authors address issues in one's home, community, country, and the world using integrative medicine and advocacy using film/video-based therapy and digital storytelling. The book highlights psychological trauma and how one can cope with the overwhelming triggers in today's world. It represents an articulate and comprehensive analysis of the ways in which traumatic human experience impacts, and is modified by, film and video media. Representing a rich and diverse range of perspectives on trauma through the lens of a camera, the authors document important examples of moments in which artistic expression becomes human resilience. Demonstrating how the language of film can facilitate watching, processing, and discussing images of trauma in therapy, in the home, in the community, and in the world, this volume will be of interest to educators and mental health practitioners with an interest in advancing psychotherapy and counseling techniques.
Part I: Introduction -- Chapter 1: Film/Video-Based Therapy TM and Virtual Reality -- Psychological Trauma -- Definition of Film/Video-Based Therapy" -- Somatic Experiencing and Trauma -- Bessel Van Der Kolk and Trauma: The Body Keeps the Score -- Dr. Albert "Skip" Rizzo: Exposure Therapy and VR -- The Mandalorian, Virtual Filmmaking, and the Unreal Engine
Film/Video-Based Therapy", Trauma Backstory, and Chapter Summaries -- Part II: Trauma in the Home, City, State/Province -- Part III: Trauma in the United States -- Part IV: Trauma in the World -- Introduction to Volume 2 -- Conclusion -- References -- Part II: Trauma in the Home, City, State/Province -- Chapter 2: "No Longer under Water": The Role of Metaphors in Trauma Re-Storying -- Trauma is in the Body -- How the Body Reacts to Threat: Polyvagal Theory -- Embodied Cognition -- The Role of Metaphors -- Art Imitating Life for Healing -- In Conclusion -- References
Chapter 3: The Application of Neurocinematics within Trauma Therapies and Integrative Practices -- Introduction -- Integrative Approaches to Trauma Therapy -- The Neuroscience of Trauma -- Neurocinematics -- Applying Neurocinematics to Psychotherapy -- Neurocinematics, Trauma Therapy, and Integrative Practices -- Clinical and Ethical Considerations -- Discussion -- References -- Chapter 4: Creating Videogames for Psychotherapy -- Introduction -- The Potential for Videogame-Based Psychotherapy -- Videogame Creation Methods -- Therapeutic Applications for Videogames with User-Generated Content -- Chapter 5: My Journey through Breast Cancer-Introduction-Starting My Digital Journal-Refining My Digital Journal Process-Going Deeper-Concerns-Note-References-Part III: Trauma in the United States-Chapter 6: Process Language and Its Impact: Making a Digital Cancer Narrative with Adolescent and Young Adult Cancer Patients and Survivors-Introduction-Background-Literature Review-AYA Cancer Challenges-Modern Technology and Filmmaking-Why Do Digital and Video Narratives Work?-Current Study-Methods-Recruitment and Participant Criteria -- Testing Procedure -- Measures -- Video Analyses -- Results -- Demographics -- Main Analyses -- Discussion -- Limitations -- Future Directions -- Conclusion -- References -- Chapter 7: Creating Impact through Trauma-Informed Drama Therapy using Videos and Films: The Efficacy of Purposeful Performance -- Introduction -- Trauma and the Body -- Drama Therapy Defined -- The Importance of Aesthetic Distance with Trauma -- Creating Educational and Therapeutic Impact using Trauma-Informed Drama Therapy in a Documentary Film: Standing Tall -- Positive Educational and Therapeutic Outcomes
Includes bibliographical references and index.
Keywords: Psychotherapy; Motion pictures in psychotherapy